A new large gomphodont from the Triassic of South Africa and its implications for Gondwanan biostratigraphy. Issue 2 (4th March 2021) - Tolchard, Frederick; Kammerer, Christian F.; Butler, Richard J.; Hendrickx, Christophe; Benoit, Julien; Abdala, Fernando; Choiniere, Jonah N.
ABSTRACT: A partial skull (BP/1/7976) of a very large cynodont from the Middle Triassic Cynognathus Assemblage Zone ( Cricodon-Ufudocyclops subzone) of South Africa is described. The specimen represents a new gomphodont taxon, Impidens hancoxi, gen. et sp. nov., diagnosed by five sectorial teeth constituting just over half of the length of the upper postcanine tooth row, and enlarged canine and incisor teeth. BP/1/8123, a skull fragment also from the Cricodon-Ufudocyclops subzone, and AMNH FARB 24421, a partial skull from the upper Fremouw Formation of Antarctica, are also referred to the new species. The presence of this taxon in both the upper Fremouw Formation and Cricodon-Ufudocyclops subzone strengthens evidence of biostratigraphic correlation between these units. Impidens hancoxi, with an inferred skull length of up to 460 mm, was a large-bodied and likely omnivorous gomphodont, and may have played the role of apex predator within the tetrapod fauna of the Cricodon-Ufudocyclops subzone.